Fabry-Pérot-multichannel spectrometer tandem for ultra-high resolution Raman spectroscopy - Rozas, Guillermo (2014)
We present a novel ultra-high resolution Raman spectroscopy technique based in a Fabry-Pérot/triple spectrometer tandem with multichannel acquisition. We describe the system, detail the calibration process, and experimentally test the technique, showing that effective finesses in excess of 1000 are possible. The technique is specifically tailored for low intensity, complex and spectrally extended Raman spectra, providing shorter acquisition times with respect to similar tandem systems with monochannel detectors.